THE IMPLEMENTATION OF PRODUCTIVE ZAKAT UTILIZATION IN ECONOMIC EMPOWERMENT OF ZAKAT RECIPIENTS: A CASE STUDY OF THE NATIONAL AMIL ZAKAT AGENCY, CIAMIS REGENCY - Moh Irfan Nurmaki; Sumarni Sumarni (Syari'ah Economics, 2022)
This study aimed to determine the program and implementation of zakat utilization at the National Amil Zakat Agency, Ciamis Regency. The research method used is the descriptive qualitative method, namely identifying the state of objects or events to draw conclusions that apply in general. Data collection techniques were carried out by observation, interviews, documentation, and triangulation. Meanwhile, data analysis includes data reduction, data presentation, and conclusion. The study results show that zakat funds are utilized consumptively, such as giving rice to the poor to fulfill their daily and productive lives. In contrast, zakat funds are channeled into developing businesses. The productive zakat utilization program of Baznas Ciamis Regency is BMUK (Small Business Capital Assistance) in the form of money and livestock (goats). The implementation of BMUK funds is channeled to people who are classified as poor and already have businesses so that the funds continue to roll. As a result, their interactions are more advanced and are used for productive things so that the recipients of this assistance are more independent in running their businesses so that their standard of living is increased. Therefore, the utilization of productive zakat in Baznas Ciamis Regency is said to have succeeded because the community can feel the benefits, and the development of its business has also increased, seen from the independence of mustahik and the ability of mustahik to give infaq.